2016
DOI: 10.1007/s10863-016-9681-9
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and mutational studies of the adenosine diphosphate ribose hydrolase from Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis represents one of the world's most devastating infectious agents – with one third of the world's population infected and 1.5 million people dying each year from this deadly pathogen. As part of an effort to identify targets for therapeutic intervention, we carried out the kinetic characterization of the product of gene rv1700 of M tuberculosis. Based on its sequence and its structure, the protein had been tentatively identified as a pyrophosphohydrolase specific for adenosine diphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…S9 ). Mutations in Glu142 in M. tuberculosis ADPRase and Glu166 in human NUDT5 considerably decrease k cat , indicating that they are involved in the deprotonation of the water molecule ( 30 , 45 ). However, mutational analysis of T. thermophilus ADPRase revealed that the mutants, Asp126, Glu127, Asp128, and Glu129, on the equivalent loop retain normal activity ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…S9 ). Mutations in Glu142 in M. tuberculosis ADPRase and Glu166 in human NUDT5 considerably decrease k cat , indicating that they are involved in the deprotonation of the water molecule ( 30 , 45 ). However, mutational analysis of T. thermophilus ADPRase revealed that the mutants, Asp126, Glu127, Asp128, and Glu129, on the equivalent loop retain normal activity ( 46 ).…”
Section: Discussionmentioning
confidence: 99%